Impact of Tourist Satisfaction Attributes on Behaviour of Sharing Tourism Experiece on Social Media - suwitho; Mustika, Hindah; Aulia Pradhani, Fastha (MATRIK: JURNAL MANAJEMEN, STRATEGI BISNIS, DAN KEWIRAUSAHAAN, 2023)
Tourist satisfaction is an emotion that is felt by visitors when they there are in a place, in this case a tourism place. The satisfaction felt by visitors makes certain behaviours, which in this case share information using social media. This study examines and analyzes the predictors of tourist satisfaction and tourist engagement on the behaviour of sharing tourism experience on social. This study had 115 respondents, using the SEM-PLS analysis technique the results showed that all influence tests were acceptable. Novelty in this study is the existence of tourist engagement that is able to make something unique because both the visitor and the place visited have an emotional engagement